The New Materialism - Feibleman, J.K. author. aut Link
190 p.
Keywords: A wholly new theory of matter has been advanced in the last half century by modern physics, but there has been no new theory of ma terialism to match it. The occurrence of a revolution of such magni tude in science will have to be understood as calling for a corresponding one in philosophy. The present work is an attempt to make a start in that direction. Grateful acknowledgment is hereby made to the Editors of the fol lowing journals for permission to reprint articles which first appeared in their pages: to Darshana for "Human Nature and Institutions"; to Diogenes for "Full Concreteness and the Re-Materialization of Matter"; to Perspectives in Biology and Medicine for "The Ambiva lence of Aggression and the Moralization of Man"; to Philosophy and Phenomenological Research for "Formal Materialism Reconfirmed" (which appears here revised and extended as "Formal Materialism: The New Version"), and for "Artifactualism: The Origin of Man and His Tools"; to Philosophy Today for "How Abstract Objects Survive"; to Religious Studies for "A Religion for the New Materialism"; and to Tulane Studies in PhilosoPhy for "A Material Theory of Reference. " PART ONE INTRODUCTION AND METHOD CHAPTER I THE SUBJECTIVE DIGRESSION Every philosophy endeavors to be as comprehensive as possible, and when philosophers speak they do so for the whole world.